THE RELATIONSHIP BETWEEN EDUCATION EXPENDITURE, HEALTH EXPENDITURE AND FINAL EDUCATION LEVEL TOWARDS THE HUMAN DEVELOPMENT INDEX FROM A SHARIAH ECONOMIC PERSPECTIVE : EVIDENCE FROM10 PROVINCES WITH THE LOWEST HDI IN INDONESIA - Julistia, Ira; Kurniawan, Muhamad; Hasimi, Diah Mukminatul (LPPM STIE Muhammadiah Bandung, 2025)
Several areas still have relatively low HDIs, despite the government's increased funding for education and health and focus on raising the final education level. The true impact of the last educational level on the quality of life and the efficacy of public expenditure are called into doubt by this. Spending on education, health care, and total education in connection to Indonesia's Human Development Index (HDI) is the focus of this research. This study used quantitative research methods that are associative in nature. The data used are secondary datasets derived from panel data collected from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance of the Ministry of Finance (DJPK MENKEU) for the years 2014–2023. The 10 provinces named Maluku Province, Central Sulawesi, Gorontalo, North Maluku, West Nusa Tenggara (NTB), West Kalimantan, West Sulawesi, East Nusa Tenggara (NTT), West Papua, and Papua are the subject of the study object, which covers the period 2014–2024 and is centered on Indonesia. Eviews 10 software was used for the analysis. The results of the study provide facts that education spending and health spending affect the Human Development Index (HDI). The final level of education does not affect the Human Development Index (HDI). The integration of Islamic economic principles in increasing the Human Development Index (HDI) that human development must include material and spiritual aspects in a balanced manner. Principles such as distributive justice, social responsibility, and fulfillment of basic needs are the basis of the Islamic Economic perspective.